Association between the TOX3 rs3803662 C>T polymorphism and recurrent miscarriage in a southern Chinese population. Issue 9 (27th August 2019) - Huang, Wendong; Zhou, Huazhong; Li, Qisen; Pi, Lei; Xu, Yufen; Fu, LanYan; Yang, Yanfang; Lu, Zhaoliang; Che, Di; Gu, Xiaoqiong
Abstract: Background: Studies have shown that some genetic polymorphisms associated with breast cancer susceptibility may also be associated with abortion. The TOX3 gene plays a key role during the onset of breast cancer, and reproductive factors such as abortion are risk factors for breast cancer. However, there is currently no study describing the relationship between the TOX3 rs3803662 C>T polymorphism and the risk of recurrent miscarriage. Therefore, we investigated whether the TOX3 rs3803662 C>T polymorphism is associated with recurrent miscarriage susceptibility in this case‐control study. Methods: We recruited 248 recurrent miscarriage patients and 392 healthy controls from the southern Chinese population and performed genotyping using the TaqMan method. Results: The results showed no evidence that TOX3 rs3803662 C>T is associated with recurrent miscarriage (CT and CC: corrected OR = 1.038, 95% CI = 0.737‐1.461, P = .8321; TT and CC: adjusted OR = 0.989, 95% CI = 0.591‐1.656, P = .9659; dominant model: adjusted OR = 1.027, 95% CI = 0.742‐1.423, P = .8712; recessive model: adjusted OR = 0.969, 95% CI = 0.600‐1.566, P = .8975). Conclusion: According to this study, the TOX3 rs3803662 C>T polymorphism may not be associated with recurrent miscarriage in the southern Chinese population. A larger multicenter study is needed to confirm the results.